Indicadores físicos de calidad de suelo en áreas con sistemas agrosilvopastoriles - Zambrano Terán, Diana Elizabeth (2020)
The search for sustainable agricultura, base don technologies that are not aggressive to the enviroment, has marked the development of agroforestry production systems as a more appropriate option, once tres, crops and animals are adopted in concept of imitation of natural ecosystems. In this contex, the presents bibliographic review aims to describe the effects of soil physical indicators in areas with agrosilvopastoral systems (SASP) contribute to the sustentainability of soil quality, they also have a socio-economic importance, due to their food production and woody component of the system that provides firewood, fodder, Wood, shade that reduces heat strees in animals, also contributing organic matter to the soil, which contributes to the recycling of nutrients. Also representing a factor of stability and security due to the timber trees that are a reserve of standing capital for rural families. Various research works show that agrosilvopastoral systems are an alternative for agroecological production that helps to have better long-term yields, due to its effects on the physical indicators of the soil. Base don the above, it is concluded that the role of agrosilvopastoral systems is to diversity production, improve soil quality, based on reducing the use of agricultural machinery and conserving the residues of the components that work in association in this production system on the ground surface.